Locoregional therapies in patients with intrahepatic cholangiocarcinoma: A systematic review and pooled analysis. (September 2021) - Edeline, Julien; Lamarca, Angela; McNamara, Mairéad G.; Jacobs, Timothy; Hubner, Richard A.; Palmer, Dan; Groot Koerkamp, Bas; Johnson, Philip; Guiu, Boris; Valle, Juan W.
Highlights: A growing literature exist as regards to locoregional treatment of intra-hepatic cholangiocarcinoma. The current review identified an extensive literature on this topic. However, the quality of the studies and of the reporting was insufficient in most case to draw definitive conclusions. Only for ablation was the results sufficiently consistent to allow for recommendations of use in patients unable to undergo surgery. For the other treatment modalities, this review provides benchmark for designing future clinical trials. Abstract: Background: Locoregional treatments (LRT) including radioembolisation (SIRT), transarterial chemo-embolisation (TACE), hepatic arterial infusion (HAI) of chemotherapy, external beam radiotherapy (EBRT) and ablation have been studied for the management of intrahepatic cholangiocarcinoma (iCC). The aim of this systematic review was to provide outcome benchmarks for clinical trial design. Methods: Identification of studies reporting outcomes of patients treated with LRT for iCC was performed using PubMed and Embase. Pooled weighted means were calculated for progression-free survival (PFS) and overall survival (OS); meta-analysis of proportions was used for estimation of pooled response rate. Results: 6325 entries were reviewed; 93 studies were eligible, representing 101 cohorts and 3990 patients: 15 cohorts (645 patients) for ablation, 18 cohorts (541 patients) for EBRT, 27 cohorts (1232 patients) for SIRT, 22 cohorts (1145 patients) for TACE, 16 cohorts (331 patients) for HAI and 3 cohorts (96 patients) not pooled. 74% of the studies were retrospective, 99% non-randomised. The pooled mean weighted OS was 30.2 months (95% confidence interval (CI): 21.8–38.6) for ablation, 18.9 (14.2–23.5) for EBRT, 14.1 (12.1–16.0) for SIRT, 15.9 (12.9–19.0) for TACE and 21.3 (15.4–27.1) for HAI. The pooled complete response rate was 93.9% for ablation. When analysed together, SIRT, TACE and HAI had a pooled mean weighted OS of 15.7 months, and 25.2 months for patients treated in first-line with concomitant systemic chemotherapy. Conclusions: Available literature on LRT for iCC was heterogeneous and of insufficient quality to make strong recommendations. Ablation achieved satisfactory outcomes, and may be recommended when surgery is not feasible.